Impact of 3D-Printing Technologies on the Transformation of Industrial Production in the Arctic Zone - Evgenii A. Konnikov; Olga A. Konnikova; Dmitriy G. Rodionov (Resources, 2019)
Today the process of transition to a new technological order has become evident to everyone, especially in developed countries. One of the most urgent areas for ensuring the long-term competitiveness of industrial enterprises is the development of the Arctic zone. This region has many economic and logistical difficulties, the solution of which may lie in the use of advanced technologies of the new technological order, for example, 3D-printing technologies. The aim of the article is to study the transformation of the cost structure of industrial products as a result of integration of 3D-printing technologies into the production process of industrial enterprise operating in the Arctic zone. It was found that the structure of the main cost elements varies greatly, due to the ambiguity of replacing computer numerical control (CNC) (or other classical shaping technologies) with 3D-printing technologies, as well as the specifics of supply chains, which is quite urgent for the Arctic region. The results of empirical study necessitate the development of tools for predicting the economic viability of integrating 3D-printing technologies into the technological processes of industrial enterprises operating in the Arctic zone. Within the article, the authors substantiated and developed a fuzzy-multiple model for assessing the level of investment attractiveness of integration of 3D-printing technologies into the production process of an industrial enterprise operating the Arctic zone. One of the aims of this model is to answer the question of whether an enterprise should invest in a technological transition to 3D-printing technologies.